2021
DOI: 10.1212/wnl.0000000000012236
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Clinical Features in X-Linked Myotubular Myopathy Carriers

Abstract: Objective:To characterize the spectrum of clinical features in a cohort of X-linked myotubular myopathy (XL-MTM) carriers, including prevalence, genetic features, clinical symptoms and signs, as well as associated disease burden.Methods:We performed a cross-sectional online questionnaire study among XL-MTM carriers. Participants were recruited from patient associations, medical centers and registries in the United Kingdom, Germany and the Netherlands. We used a custom-made questionnaire, the Checklist Individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…In addition to limb girdle and axial weakness, we also observed a wide range of other signs suggestive of a myopathic phenotype, such as fatigue, exercise intolerance, myalgia and muscle cramps, and mild (asymmetric) facial weakness including ptosis. In line with our previous study, 16 these signs were also reported, albeit to a lesser extent, in carriers classified as nonmanifesting. Our main finding is that 52% of XL-MTM carriers within our cohort are symptomatic based on physical examination.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition to limb girdle and axial weakness, we also observed a wide range of other signs suggestive of a myopathic phenotype, such as fatigue, exercise intolerance, myalgia and muscle cramps, and mild (asymmetric) facial weakness including ptosis. In line with our previous study, 16 these signs were also reported, albeit to a lesser extent, in carriers classified as nonmanifesting. Our main finding is that 52% of XL-MTM carriers within our cohort are symptomatic based on physical examination.…”
Section: Discussionsupporting
confidence: 92%
“…The previous analysis of a cohort of 76 carriers also showed the correlation between age and clinical severity. 16 Altogether, this might suggest a slowly progressive disease course with presentation only in later life, but underlying factors need to be further elucidated. 10 Seven manifesting carriers had not been diagnosed with manifesting carriership and had not related their symptoms to their MTM1 carriership before, confirming our hypothesis of a possible ascertainment bias in previous case series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most female XLMTM carriers were first assumed to be asymptomatic, but recent studies have shown they can have symptoms with a wide spectrum of clinical involvement from severe neonatal and generalized weakness with respiratory dysfunction to more commonly observed milder forms in adulthood [ 26 , 27 ]. Prevalence of manifesting XLMTM carriers may be higher than currently assumed as demonstrated with a new cohort of 76 female carriers published in 2021 with 51% manifesting carriers [ 28 ]. It is characteristic to observe asymmetric weakness and growth, facial involvement, ptosis, and skeletal and joint abnormalities [ 26 , 27 ].…”
Section: Mtm1 and Myotubular Myopathymentioning
confidence: 99%